Reliability Indicators of Urban Electric Network Schemes for Supply of Second and Third Category Consumers - M. A. Korotkevich; A. L. Starzhinsky (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers two schemes of the urban distributive electric network for supply of the second and third category consumers for whom indicators of reliability have been determined.As for a network scheme of the 2nd category it has been determined that while installing low-oil and vacuum switches at a distributive point the most remote transformer substation has the highest non-availability  factor which is higher of the corresponding non-availability  factor of the nearest transformer substation by 1,21–1,23 fold  accordingly.As for a network scheme of the 3rd category consumers it has been obtained the data that reliability of consumers receiving supply from bus-bars of transformer substations with 0,38 kW voltage changes  significantly (by 1,2–1,9-fold) while changing a breakpoint of the network with 10 kW voltage.